History of psychiatry in Bengal - Bandyopadhyay, Gautam Kumar (Indian J Psychiatry, 2018)
The history of psychiatry in Bengal mirrors the history of psychiatry in India. With Bengal being an important location for the East India Company, it became the locus for much infrastructure development, including the setting up of lunatic asylums. This article traces the development of psychiatric care in Bengal, from the early time of private asylums exclusively for Europeans, to psychiatric care in the present time.